Using electrical resistivity techniques (ERT and SP) for nondestructive detection of seepage channels at the Leitai heritage site, China - Kai Lu; Kaitian Li; Fan Li; Zhenyu Li; Peng Wang (Scientific Reports)
Abstract Seepage accelerates the weathering and destruction of cultural heritage sites, posing a major preservation challenge, while the concealed nature of seepage channels complicates their detection due to noninvasive requirements. In this study, we applied a comprehensive geophysical approach, integrating electrical resistivity tomography (ERT) and self-potential (SP) techniques, to image seepage channels within the Leitai heritage site. These potential seepage channels have already caused a collapse pit measuring 3.1 m × 2.7 m on the site’s surface. We began with 2D ERT surveys, which were then combined for 3D inversion to reveal the resistivity structure of the site. Subsequently, SP data were extracted along typical survey lines using interpolation algorithms, and these were inverted to supplement and verify the resistivity structure. The results from both techniques were highly consistent, indicating the presence of internal channels within the site. This comprehensive geophysical approach provides critical insights and references for the subsequent restoration efforts of the Leitai heritage site, ensuring the protection and preservation of this culturally significant landmark. Moreover, the method proposed in this study can be easily applied to the preservation of similar cultural heritage sites elsewhere.